2020
DOI: 10.1073/pnas.2001755117
|View full text |Cite|
|
Sign up to set email alerts
|

Multiorbital charge-density wave excitations and concomitant phonon anomalies in Bi 2 Sr 2 LaCuO 6+δ

Abstract: Charge-density waves (CDWs) are ubiquitous in underdoped cuprate superconductors. As a modulation of the valence electron density, CDWs in hole-doped cuprates possess both Cu-3dand O-2porbital character owing to the strong hybridization of these orbitals near the Fermi level. Here, we investigate underdoped Bi2Sr1.4La0.6CuO6+δusing resonant inelastic X-ray scattering (RIXS) and find that a short-range CDW exists at both Cu and O sublattices in the copper-oxide (CuO2) planes with a comparable periodicity and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
5
29
0
Order By: Relevance
“…For the copperoxygen bond-stretching mode, a sin 2 (h) dependence of intensity for Q = (h, 0) is expected in the absence of charge order (16,(25)(26)(27). Recent RIXS studies, on different cuprate systems, have observed bond-stretching phonon intensities in good agreement with this theoretical modeling (20,21,25,26). It is also in accord with the intensities measured above T LTT in LESCO (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For the copperoxygen bond-stretching mode, a sin 2 (h) dependence of intensity for Q = (h, 0) is expected in the absence of charge order (16,(25)(26)(27). Recent RIXS studies, on different cuprate systems, have observed bond-stretching phonon intensities in good agreement with this theoretical modeling (20,21,25,26). It is also in accord with the intensities measured above T LTT in LESCO (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Phase excitations of stripes couple to the lattice and create a splitting of the in-phase and out-of-phase oscillation modes (35). However, the phonon anomaly is expected (35) to exist within a narrow (17,19,20). This is supported by a nonmonotonically increasing phonon intensity versus momentum and an excitation energy softening that exceeds expectations for EPC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, as they do affect the shape of the Fermi surface via hybridization between energy bands derived from the CuO 2 planes and the CuO chains, they may thus indirectly influence the propensity of the electron system in the CuO 2 planes to CDW formation. The importance of electron-phonon interactions (EPI) for the formation of the CDW in the cuprates has been highlighted [9,26,41,[46][47][48][49], and research on classical CDW compounds has shown that its momentum dependence is also a critical parameter [50][51][52]. We argue here that the pronounced a=b anisotropies of EPI for high-energy phonons reported in YBCO [53,54] reflect the influence of the CuO chains on the EPI and play an important role in destabilizing the 3D a-CDW relative to the b-CDW.…”
mentioning
confidence: 99%
“…However, trends with doping do not show any clear correlation with spin-charge stripes 39 , static charge density waves 42 , or kinks in the electronic dispersion 40 , which seems to rule out conventional el-ph coupling mechanisms of the type contempleted here. Rather, it is proposed that the softening reflects coupling to a collective charge mode of the electron liquid 40,43 . In Forgan et al 32 , oxygen displacements do indeed have in-plane components, indicating that the bondstretching modes contribute alongside the buckling mode, but the out-of-plane components are dominant, and we make the simplifying approximation that the in-plane component can be neglected.…”
mentioning
confidence: 99%